EFFECTS OF INFESTATION BY SYSTOLE CORIANDRI (GUSSAKOVSKY) (HYMENOPTERA: EURYTOMIDAE) ON GERMINATION AND OIL CONTENT OF CORIANDER SEEDS (Acta Entomológica Chilena, 2022)
Evaluations of infestation by Systole coriandri and tests of germination and oil contení of fruits of coriander apparently undam aged or with 1-2 mericarps (seeds) damaged, of sam ples obtained in central Chile, demonstrated variable infestation and germ ination levels among locations. Dissecting seeds revealed 3.8-14.0% infestation levels in apparently undamaged fruits, with linear correlation coefficients (r) of -93.4 betw een infestation and germ ination; fruits with one dam aged mericarp presented an r coefficient of -94.0 between these param eters.Fruits with both mericarps dam aged did not present germ ination, dem onstrating that S. coriandrilarvae, dam age the embryo. A lso, damage to 1 or 2 m ericarps reduced oil content by 16.7 and 42.0%, respectively, from the levels in fruits apparently undamaged.